2019
DOI: 10.1177/0391398819876286
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to bone tissue engineering

Abstract: Bone tissue has the capability to regenerate itself; however, defects of a critical size prevent the bone from regenerating and require additional support. To aid regeneration, bone scaffolds created out of autologous or allograft bone can be used, yet these produce problems such as fast degradation rates, reduced bioactivity, donor site morbidity or the risk of pathogen transmission. The development of bone tissue engineering has been used to create functional alternatives to regenerate bone. This can be achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 116 publications
0
107
0
3
Order By: Relevance
“…It has been shown that this induced membrane can possess osteoinductive, osteogenic and angiogenic properties, and several clinical studies have demonstrated satisfactory results [38]. Especially implant bed vascularization via angiogenesis has been recognized as a basic factor for successful (bone) tissue regeneration [39,40]. Thus, to date, different strategies have focused on the development of materials that can promote vascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that this induced membrane can possess osteoinductive, osteogenic and angiogenic properties, and several clinical studies have demonstrated satisfactory results [38]. Especially implant bed vascularization via angiogenesis has been recognized as a basic factor for successful (bone) tissue regeneration [39,40]. Thus, to date, different strategies have focused on the development of materials that can promote vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Another goal for the future development of a variety of biomaterials is to induce a specific immune response that can further stimulate (bone) tissue healing [12]. In this context, the inflammatory tissue reaction cascade to biomaterials has been elucidated in recent decades, and especially the macrophage has been identified as an important key factor to guide the tissue regeneration process [14,40]. In broad terms, there are two main subforms of macrophages, i.e., proinflammatory M1-and anti-inflammatory M2-macrophages [41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, despite the similarity in terms of materials and morphological features between the cortical and trabecular bone, the differences in porosity confer them peculiar mechanical properties. In particular, while the cortical bone is characterized by high compressive strength , the trabecular bone stregth is one or two order of magnitude less (2 to 12 MPa) [3,7]. On the other hand, the trabecular bone reacts with high energy storage capability that reflects on increases of its length up to an order of magnitude higher than the cortical one (50% vs 2%) [7].…”
Section: Bone Mechanical Propertiesmentioning
confidence: 99%
“…The secondary bone is on turn constituted of the cortical bone, that comprises 80% of the skeleton and it is characterized by low porosity (5-30%) and the trabecular one, with high porosity spanning from 30% to 95%. Native bone tissue physical characteristics are summarized in Table 1 [3,4]. The functional unit of the mature bone is the osteon, also called the Haversian system.…”
Section: Anatomymentioning
confidence: 99%
“…Small bone defects usually heal with the formation of new bone, with no to minimal scar tissue. However, large bone defects (fracture gap more than 2.5 cm) such as osteoporosis and osteonecrosis caused by trauma, tumour or infection require a larger-scale bone regeneration, which is beyond the self-healing capacity of a normal bone, thereby necessitating external bone repair approaches [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%